2013
DOI: 10.1177/0022034513516465
|View full text |Cite
|
Sign up to set email alerts
|

Carbodiimide Inactivation of MMPs and Effect on Dentin Bonding

Abstract: The use of protein cross-linking agents during bonding procedures has been recently proposed to improve bond durability. This study aimed to use zymography and in situ zymography techniques to evaluate the ability of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) cross-linker to inhibit matrix metalloproteinase (MMP) activity. The hypotheses tested were that: (1) bonding procedures increase dentin gelatinolytic activity and (2) EDC pre-treatment prevents this enzymatic activity. The zymographic assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 30 publications
5
98
0
8
Order By: Relevance
“…19,20,34 Additionally, EDC is able to preserve the resin-dentin bond over time. 35 In the medical field, EDC has been used to reinforce different structures for tissue engineering applications and has shown satisfactory biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,34 Additionally, EDC is able to preserve the resin-dentin bond over time. 35 In the medical field, EDC has been used to reinforce different structures for tissue engineering applications and has shown satisfactory biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Since lower biodegradation rates and high mechanical properties of collagen are desirable, the use of collagen cross-linking agents in adhesive procedures has gained increased popularity in recent years [63,66]. The use of glutaraldehyde, proanthrocyanidin and genipin [123], riboflavin [124], as well as tannic acid [122] and carbodiimide [70] has been proposed to enhance the mechanical and structural stability of dentin collagen, leading to a stable dentin matrix network that, after resin infiltration, should provide a durable hybrid layer [125][126][127][128][129]. Moreover, collagen cross-linking molecules have been reported to improve the resistance of uncross-linked or mildly cross-linked collagen matrices to degradation by bacterial collagenases [130,131], potentially contributing to the stabilization of the resin-dentin interface over time.…”
Section: Collagen Cross-linking Agentsmentioning
confidence: 99%
“…5A, B; Mazzoni et al 2012;Mazzoni et al 2014). Although previous studies demonstrated the presence and activity of endogenous proteolytic enzymes in human dentin, evidence of the activity of endogenous dentin MMPs within resin-bonded HLs was lacking.…”
Section: Role Of Mmps In Hl Degradationmentioning
confidence: 99%
“…The potential of cross-linkers is related to the possibility of improving the mechanical strength of the collagen network (Bedran-Russo et al 2014), improving the resistance to enzymatic degradation, and inactivating exposed MMPs bound to matrix collagen (Liu et al 2011;Tjäderhane et al 2013b). Together, this leads to a stable dentin matrix network, which ultimately could determine the formation of a stable HL (Cova et al 2011;Mazzoni, Angeloni, et al 2013;Tjäderhane et al 2013b;Bedran-Russo et al 2014;Mazzoni et al 2014). …”
Section: Therapeutic Mmp Inhibitors In Caries Progression and Bond Stmentioning
confidence: 99%